THE EFFECTIVENESS PF PROJECT-BASED LEARNING FOR BIOLOGY CLASS IN DEVELOPING THE SCIENCE PROCESSING SKILLS AND CREATIVITY OF HIGH SCHOOL STUDENTS - Milla, Daindo; A W, Jufri; H, Soepriyanto (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This research aims to measure the effectiveness of Project-based learning in developing the science processing skills and creativity of XI grade students of SMAN 1 Wewewa Timur and SMA Swasta Manda Elu in Sumba Barat Daya, NTT. This research employs quasi-experimental design. The effectiveness of the project-based learning of biology is known after the improvement in the 1st, 2nd, and 3rd test as well as the observation of students’ science processing skills. The result of the research shows that the learning approach, project-based learning, is effective to improve students’ science processing skills. The conclusion came from the observation score of 79.5%. The students experienced improvement through test 1 to test 3. In this case, they got the average score of 44 in the 1st test, 49 in the 2nd test, and 60 in the 3rd test. The gain of the score was 0.2 or categorized as low. Meanwhile, the students’ creativity score was 69%. In summary, project-based learning can develop students’ science processing skills and creativity.